Sleep Insights A Conversation with Matthew Walker. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
Howard Burton was the Founding Director of Canada's Perimeter Institute for Theoretical Physics. He holds a PhD in theoretical physics and an MA in philosophy. This book is part of an expanding series of 100+ Ideas Roadshow conversations, each one presenting a wealth of candid insights from a leading expert in a focused yet informal setting to provide a uniquely accessible window into frontline research and scholarship that wouldn't otherwise be encountered through standard lectures and textbooks.